Nils Astrup and indigenous African cultures: A study in evolving missionary attitudes - Hale, Frederick (Journal for the study of religion, 2015)
It has often been alleged that during the nineteenth and twentieth centuries European missionaries evinced little respect for the indigenous peoples whom they evangelised and otherwise sought to influence through Christian ministry. Considerably less frequently, however, have such assertions been substantiated with detailed case studies to demonstrate possible attitudinal shifts over time as the missionaries in question became better acquainted with African cultures and folkways. The present article, a response to M.M. Sepota's 'The Destruction of African Culture by Christianity' which was published in the Southern African Journal for Folklore Studies, examines the attitudes of one key individual, Hans Astrup, who headed the Church of Norway Schreuder Mission from his arrival in Natal in 1883 until he felt confident about expanding his agency's field into what are now Mozambique and Swaziland.